Growth and litter accumulated in pure stands of Luehea divaricata Mart. and Parapiptadenia rigida (Benth.) Brenan in the Southwest Region of Paraná - Brun, Eleandro José; Brun, Flávia Gizele König; Frigotto, Taciana; Ribeiro, Raquel Rossi; Mezzalira, Carlos César (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
Were quantified the accumulated litter, the understory biomass and dendrometric variables in pure stands of Luehea divaricata (açoita-cavalo) and Parapiptadenia rigida (angico-vermelho), both with six years old, in one experimental area of UTFPR Campus Dois Vizinhos. In each of three plots with 400 m², randomly distributed in the stands, were sampled, four samples of accumulated litter above the soil and the above ground biomass of understory plants. The total quantity of the accumulated litter and understory biomass varied between 18.96 Mg ha-1 to Açoita-cavalo (46.0% leaves; 30.2% branches; 11.7% miscellany and 12.1% understory) and 20.41 Mg ha-1 to angico-vermelho (51.4% leaves; 22.3% branches; 14.3% miscellany and 12.0% understory), with similarity in the total quantity and variations between the fractions, explained by the auto ecology of the species. Açoita-cavalo showed diameter at breast height (DBH) of 7.7±1,8 cm, total height (Ht) of 8.1±0,5 m, with 1250 trees ha-1 and basal area of 6.7 m² ha-1, with bifurcation in most of the stems, with average of 1.8 trunks by tree. To angico-vermelho, the DBH was 8.6±0,6 cm, Ht of 6.6±0,6 m, with 450 trees ha-1 and basal area of 3.1 m² ha-1, with lower occurrence of bifurcations, with 1.1 trunks by tree. The studied species showed similar growth, still of the angico-vermelho present less density of trees, with the occurrence of more number of mortality of plants, because in the implantation, the adopted spacing was 2 m x 2 m for both species.